Trade Flows, Prices, and The Exchange Rate Regime - Philippe Bacchetta; Eric van Wincoop (Swiss National Bank, Study Center Gerzensee, 2000)
This paper examines the relationship between the exchange rate regime and trade flows using a general equilibrium model based on Bacchetta and van Wincoop (AER, 2000). We show that in general the link between trade and the exchange rate regime is ambiguous and that it depends in particular on the nature of macroeconomic shocks and consumer preferences. A critical aspect is the pricing strategy adopted by monopolistically competitive firms. Trade is more likely to be affected by the exchange rate regime if firms price in buyers' currency, or price to market (PTM), than if they price in producers' currency (PCP). We show, however, that PCP is not an equilibrium under reasonable parameters when international capital markets are not available. In contrast, when markets become more complete, firms tend to switch to PCP.
Keywords: F31; F33; F41; 330; Wechselkurssystem; Internationale Wirtschaft; Wohlfahrtsanalyse; Allgemeines Gleichgewicht; Theorie